Description of Elementary School Students' Ability to Use Local Letters - Arif Widodo; Helmi Anisah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
Local letters are one part of the nation's cultural literacy. The existence of local letters must be preserved. Various efforts have been made to preserve local letters, one of which is by integrating local letter learning into local content subjects in elementary schools. One of the local letters owned by the Indonesian people is the Satera Jontal letter. Satera Jontal is the original script of the Samawa tribe, one of the major ethnic groups in West Nusa Tenggara. This study aims to determine the literacy ability profile of elementary school students to the local letters of Satera Jontal. The research was conducted at an elementary school in Sumbawa. The type of research used is descriptive qualitative. Collecting data using questionnaires and interviews. The subjects in this study were elementary school students, totaling 17 students. Based on the results of data collection, it can be seen that there are no students who are able to read and write Satera Jontal letters. Students are only able to recognize the shape and name of the Satera Jontal letters but are not able to assemble them into a sentence. The number of students who are able to recognize the letters of Satera Jontal is very few, namely less than 30% of the total research subjects. This kind of condition is a very serious threat to the preservation of local letters. There needs to be a real intervention by related parties so that local letters do not become extinct in the future, one of which is re-teaching local letters into local content subjects.